Intervening at the Margins: Preschool Teachers’ Perception of Disability Intervention in Rural Areas - Noviana Mustapa; Widya Rizky Pratiwi; Dwi Rezki Hardianto Putra Rustan; Juhana; Anugrah Murtini; Samihah Mahamud (PLD UIN Sunan Kalijaga, 2025)
This study employed a quantitative descriptive survey design to examine preschool teachers’ perceptions of interventions for children with disabilities in rural areas of Banten, Indonesia. Data were collected from 62 preschool teachers using a 25-item questionnaire covering five domains: understanding of disability, early identification, intervention planning, classroom implementation, and evaluation. Descriptive statistical analysis was used to interpret the data. The findings indicate that teachers generally hold positive attitudes toward inclusive education and recognise the importance of differentiated learning approaches. However, notable gaps remain in teachers’ practical competence and confidence, particularly in developing Individual Learning Plans and implementing interventions independently in classroom settings. Professional collaboration was also perceived as limited due to insufficient guidance and access to specialist support. These findings highlight the need for targeted professional development to strengthen teachers’ capacity to implement inclusive practices effectively, especially in rural contexts where access to training and support remains constrained. Penelitian ini menggunakan desain survei kuantitatif deskriptif untuk mengkaji persepsi guru PAUD terhadap intervensi bagi anak dengan disabilitas di wilayah pedesaan Banten. Data dikumpulkan dari 62 guru PAUD melalui kuesioner berisi 25 butir yang mencakup lima aspek: pemahaman tentang anak dengan disabilitas, identifikasi dini, perencanaan intervensi, pelaksanaan di kelas, dan evaluasi. Data dianalisis menggunakan statistik deskriptif. Hasil penelitian menunjukkan bahwa guru umumnya memiliki sikap positif terhadap pendidikan inklusif dan memahami pentingnya pembelajaran yang beragam. Namun, masih terdapat kesenjangan pada kompetensi praktis dan kepercayaan diri, khususnya dalam penyusunan rencana pembelajaran individual dan pelaksanaan intervensi di kelas. Selain itu, kolaborasi profesional masih terbatas akibat kurangnya bimbingan dan akses terhadap dukungan. Temuan ini menegaskan perlunya pelatihan profesional yang lebih terarah untuk memperkuat kapasitas guru dalam menerapkan praktik pendidikan inklusif secara efektif, terutama di wilayah pedesaan.